A GATA Transcription Factor Recruits Hda1 in Response to Reduced Tor1 Signaling to Establish a Hyphal Chromatin State in Candida albicans - Lu, Yang (Public Library of Science, 2012)

(untitled)
Candida albicans is an important opportunistic fungal pathogen of immunocompromised individuals. One critical virulence attribute is its morphogenetic plasticity. Hyphal development requires two temporally linked changes in promoter chromatin, which is sequentially regulated by temporarily clearing the transcription inhibitor Nrg1 upon activation of the cAMP/PKA pathway and promoter recruitment of the histone deacetylase Hda1 under reduced Tor1 signaling. Molecular mechanisms for the temporal connection and the link to Tor1 signaling are not clear. Here, through a forward genetic screen, we report the identification of the GATA family transcription factor Brg1 as the factor that recruits Hda1 to promoters of hypha-specific genes during hyphal elongation. BRG1 expression requires both the removal of Nrg1 and a sub-growth inhibitory level of rapamycin; therefore, it is a sensitive readout of Tor1 signaling. Interestingly, promoters of hypha-specific genes are not accessible to Brg1 in yeast cells. Furthermore, ectopic expression of Brg1 cannot induce hyphae, but can sustain hyphal development. Nucleosome mapping of a hypha-specific promoter shows that Nrg1 binding sites are in nucleosome free regions in yeast cells, whereas Brg1 binding sites are occupied by nucleosomes. Nucleosome disassembly during hyphal initiation exposes the binding sites for both regulators. During hyphal elongation, Brg1-mediated Hda1 recruitment causes nucleosome repositioning and occlusion of Nrg1 binding sites. We suggest that nucleosome repositioning is the underlying mechanism for the yeast-hyphal transition. The hypha-specific regulator Ume6 is a key downstream target of Brg1 and functions after Brg1 as a built-in positive feedback regulator of the hyphal transcriptional program to sustain hyphal development. With the levels of Nrg1 and Brg1 dynamically and sensitively controlled by the two major cellular growth pathways, temporal changes in nucleosome positioning during the yeast-to-hypha transition provide a mechanism for signal integration and cell fate specification. This mechanism is likely used broadly in development.